Improvement of methods of early potato cultivation in the zone of light chestnut saline soils of the Astrakhan region - A. N. Bondarenko; A. V. Tyutyuma (Новые технологии, 2023)
Potato is grown almost everywhere, mainly in areas with a temperate climate and the most favorable weather conditions for the growth and development of this crop. Various varieties of potatoes are also grown throughout the Astrakhan region, but the very harsh arid climate of natural conditions, as well as soils with low humus content, significantly affect the productivity of this crop.The use of improved agricultural technologies for cultivating various varieties of early potato is today a very important area in vegetable growing in the Lower Volga region. In this connection the search for modern resource-saving agrotechnological methods for cultivating early potatoes, which would contribute to high yields at lower production costs, is very relevant.Therefore, the main goal of the research is to study the features of early potato yield formation when using pre-planting soaking of tubers using Azotovit, Phosphatovit and Baykam EM 1 preparations on the background of various irrigation rates of 4600 m3/ha and 5200 m3/ha. The studies were carried out on an irrigated land use plot of the FSBSI «PAFSC RAS» in the period from 2019 to 2021. In the experiment generally accepted agricultural technology was used in accordance with zonal recommendations for cultivating early potato in the Lower Volga region.Relevant studies and measurements were carried out in accordance with the requirements of the field experiment methodology and research methods for potato crops.Experimental studies established that over the period of a three-year study, the minimum water consumption coefficient of 110.05 m3/t was obtained in the option with an irrigation rate of 5200 m3/ ha, in the option with treatment of tubers before planting in Azotovit preparation, while this option turned out to be the most profitable in studying. The yield in this option was 56.0 t/ha with a total cost of 489.1 thousand rubles. The cost was equal to 8.7 thousand rubles per 1 ton, net income 630.9 thousand rubles per 1 hectare. With such indicators, production profitability amounted to 129.0%.